Determination of Caffeine and Hydrogen Peroxide Antioxidant Activity of Raw and Roasted Coffee Beans Around Habru Woreda, Ethiopia Using UV-Vis Spectroscopy - Legas Muhammed B; Hussen Seid M; Habte AT (Dove Medical Press, 2021)
Beshir Legas Muhammed, Mohammed Hussen Seid, Adere Tarekegne Habte Department of Chemistry, Woldia University, Woldia, EthiopiaCorrespondence: Beshir Legas Muhammed Email legasbeshir@yahoo.comBackground: Coffee is a well-known beverage that is widely used around the world. Despite the wide use of coffee in Ethiopia, there is a lack of extensive studies addressing the issues related to the caffeine content and hydrogen peroxide antioxidant activity of varieties of coffee types, particularly in Habru woreda, Ethiopia.Objective: This study aimed to determine the caffeine content and hydrogen peroxide antioxidant activity of raw and roasted coffee beans collected directly from Habru woreda, North Wollo zone of Ethiopia.Methods: The study was conducted in Bohoro, Girana, and Wurgisa kebeles of Habru woreda, Ethiopia, by collecting 500 g of green beans of Arabica coffee without considering their variety. Then, the collected beans were divided into raw and roasted coffee to perform aqueous and dichloromethane extraction of their caffeine content and hydrogen peroxide antioxidant activity using UV-Vis spectrophotometry.Results: The amounts of caffeine in aqueous and dichloromethane extraction were in the range of 124.01− 191.27 ppm and 145.15− 200.09 ppm in raw and roasted coffees, respectively. Using the IC50 value, the hydrogen peroxide scavenging activity of the aqueous phase coffee bean extracts in Bohoro raw, Bohoro roasted, Wurgisa raw, Wurgisa roasted, Girana raw, and Girana roasted coffee were 32.17 ppm, 11.69 ppm, 26.14 ppm, 3.12 ppm, 24.83 ppm, and 11.06 ppm, respectively, while that of ascorbic acid was 6.91 ppm.Conclusion: The study showed that the highest amount of caffeine in both aqueous and dichloromethane solvent extraction was found in Bohoro’s raw and roasted coffee beans. Also, the amounts of caffeine in all coffee bean samples were safe and the antioxidant activity was excellent. In most of the samples, significant variations in the concentration of caffeine in raw and roasted coffee bean samples were observed in the two extraction solvents.Keywords: caffeine, coffee, hydrogen peroxide scavenging, UV-Vis spectroscopy